Desempeño holístico del docente y desarrollo integral en estudiantes del quinto ciclo nivel primaria del Colegio Cooperativo César Vallejo, Iquitos 2023 - Guerra D’Jesus, Juan Luis (2024)
The aim of the present study was to relate the holistic performance of teachers to the overall development of fifth-grade students at Colegio Cooperativo César Vallejo Iquitos in 2023. The methodology employed was based on a relational approach, with a cross-sectional and bivariate field design. A population and sample of 271 students were surveyed using validated questionnaires. The correlation results indicated a significant relationship between the holistic performance of teachers and the overall development of fifth-grade students at Colegio Cooperativo César Vallejo Iquitos in 2023. The obtained p-value was lower than the significance level (α = .05), leading to the rejection of the null hypothesis and acceptance of the alternative hypothesis. Additionally, the correlation coefficient (rho = .414) revealed a moderately positive relationship between both variables. In conclusion, it was found that adequate holistic performance of teachers is moderately associated with an improvement in the overall development of fifth-grade students at Colegio Cooperativo César Vallejo Iquitos in 2023.